THE INFLUENCE OF FINANCIAL ATTITUDE, FINANCIAL KNOWLEDGE, PERSONAL INCOME AND EDUCATION LEVEL ON FINANCIAL BEHAVIOUR - BINTI SUWADJI, LANTIP SUSILOWATI (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
Abstract: This study aims to examine the effect of Financial Attitudes, Financial Knowledge, Personal Income and Education Level on Financial Behavior in employees of CV Mahesa Interior District Kediri Regency partially and simultaneously. This research method used is a quantitative approach with an associative research type. The population used is employees of CV Mahesa Interior Kediri Regency. The data source is primary data, data collection methods by distributing questionnaires, samples obtained using non-probability sampling types with saturated sampling techniques. Data analysis using IBM SPSS version 26. The results showed that Financial Attitudes partially had a significant positive effect on Financial Behavior, Financial Knowledge partially had a significant positive effect on Financial Behavior, Personal Income partially had a significant positive effect on Financial Behavior, Education Level partially had a significant positive effect on the Financial Behavior. Financial Attitude, Financial Knowledge, Personal Income, and Education Level simultaneously have a significant positive effect on Financial Behavior of CV Mahesa Interior Kediri regency.